Situation Report: Hungary, 26 August 1969 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Constitution Day Celebrations Political Themes Economic Themes Hungarian Participation in the Celebration of Romanian Liberation Day Coverage of Czechoslovak Invasion Anniversary Friendship II Pipeline to Be Completed and Soviet Crude Oil Deliveries to Be Increased Editors of New Literary Periodical "Forras" Visit Yugoslavia Proposals for Strengthening "Weak" Agricultural Co-operatives An Abundant Harvest, but Inadequate Storage Capacity Agricultural Specialists' Study Tours in Yugoslavia and Italy